2021
DOI: 10.1002/jia2.25782
|View full text |Cite
|
Sign up to set email alerts
|

HIV self‐testing and oral pre‐exposure prophylaxis are empowering for sex workers and their intimate partners: a qualitative study in Uganda

Abstract: Introduction: HIV self-testing (HIVST) and oral pre-exposure prophylaxis (PrEP) are complementary, evidence-based, selfcontrolled HIV prevention tools that may be particularly appealing to sex workers. Understanding how HIVST and PrEP are perceived and used by sex workers and their intimate partners could inform prevention delivery for this population. We conducted qualitative interviews to examine ways in which HIVST and PrEP use influence prevention choices among sex workers in Uganda. Methods: Within a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 50 publications
(42 reference statements)
2
28
0
Order By: Relevance
“…However, some caution regarding the utility of HIVST for sexual decision-making is warranted; oral fluid self-test kits may be misinterpreted and have low sensitivity in acute HIV infection and in persons taking PrEP or antiretroviral therapy, which may result in false-negative results and a false sense of safety. 17,51,52 We found no evidence of behavioral risk compensation among sex workers in agreement with previous reports. 53,54 In contrast with previous studies, we observed a lower likelihood of sex acts unprotected by condoms among MSM and TGSWs but not FSWs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, some caution regarding the utility of HIVST for sexual decision-making is warranted; oral fluid self-test kits may be misinterpreted and have low sensitivity in acute HIV infection and in persons taking PrEP or antiretroviral therapy, which may result in false-negative results and a false sense of safety. 17,51,52 We found no evidence of behavioral risk compensation among sex workers in agreement with previous reports. 53,54 In contrast with previous studies, we observed a lower likelihood of sex acts unprotected by condoms among MSM and TGSWs but not FSWs.…”
Section: Discussionsupporting
confidence: 92%
“…Sex workers use point-of-sex testing (ie, using HIVST kits to screen paying partners) as a risk reduction strategy in settings where partners pay more for condomless sex acts. 17,[45][46][47] Studies of FSWs, MSM, and TGSWs suggest that point-of-sex testing empowers and informs sexual decision-making such as avoiding sex act or insisting on condom use with paying partners who tested HIVpositive. 11,[48][49][50] This ancillary benefit could motivate HIVST use among sex workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 In a PrEP program in Uganda, female sex workers reported using HIVST to test clients to earn more money by accepting condomless sex. 29 This “benefit” was also perceived by female sex workers in this study. Without pre-exposure prophylaxis (PrEP), there could be a risk of HIV exposure if HIVST is performed with a partner or client who was recently exposed to the virus.…”
Section: Discussionsupporting
confidence: 63%
“…The study was conducted at the Makerere University Infectious Diseases Institute research clinic in Kasangati, Uganda. Since 2018, five HIV prevention research studies among trans women and trans men have been implemented at the research facility, which is easily accessible by public transportation [ 24 ]. The research team utilizes a trans‐inclusive approach incorporating community engagement, provider sensitivity training, peer support, inclusion of trans people in research design and implementation, and as co‐investigators and members of the community advisory group, plus quarterly consultative meetings for trans people, peers and research staff.…”
Section: Methodsmentioning
confidence: 99%